Life cycle approaches for the environmental impact assessment of organizations: Defining the state of the art - Michela Rimano; Alberto Simboli; Raffaella Taddeo; Andrea Raggi (Administrative Sciences, 2019)
Organizations play a key role in reducing anthropogenic pressure on the natural environment. The first step towards improving their sustainability performances is the implementation of methodologies that take into consideration multiple environmental impact categories, as well as the entire value chain. The attention of scholars and practitioners was initially addressed to the analysis of products and processes, yet in a few cases in which they were addressed, the approaches used for organizations had a limited scope and range of use. Only in recent years have they been framed in a life cycle perspective. This article analyzes two recent life cycle-based methodologies that have their focus on the organization, namely Organization Environmental Footprint (OEF) and Organizational Life Cycle Assessment (O-LCA). The goal is to define the state of the art of their methodological and current application developments and consider the relevance that these methodologies can have, both in terms of internal and external commitment (e.g., for the supply chain actors) and of reporting and communication requirements. The research was carried out starting from scientific databases, integrating technical legislation and secondary literature. The results obtained allowed tracing the first evolutionary trends, identifying the main authors and scientific journals and highlighting the relevant issues according to the researchers. A content and bibliometric analysis was performed that included all the contributions published so far. Projects and case studies that practically applied the two methodologies were also identified and analyzed. Finally, the main differences between the two methodologies were highlighted and future developments were hypothesized.
Keywords: 350; Organisation Environmental Footprint (OEF); organizational life cycle assessment (O-LCA); ISO/TS 14072